THE ALIENATION OF CHARACTERS IN THE NOVEL "MAUSIM AL-HIJRAH ILA AS-SYAMAL" BY TAYEB SALIH BASED ON ERICH FROMM'S PERSPECTIVE - Syahrul Alfitrah Miolo; Syahra Maulina Miolo (Afshaha: Jurnal Bahasa dan Sastra Arab, 2024)
The alienation experienced by a person is often underestimated. Anyone can experience alienation depending on their personality and living conditions. This research aims: (1) to determine the form of alienation of the character "I" in the novel "Mausim al-Hijrah ila as-Syamal"; and (2) to determine the form of alienation of the character "Mustafa Said" in the novel "Mausim al-Hijrah ila as-Syamal". Researchers use a qualitative descriptive approach as a type of research and library research as a type of research. The data source in this research is the novel "Mausim Al-Hijrah ila As-Syamal" by Tayeb Salih, published in 1966. The data collection techniques in this research used reading, translation and note-taking techniques. Meanwhile, data analysis techniques are carried out by reducing data, displaying data, comparing the data/results of this research with data/results of other research, and drawing conclusions. The results of this research are: (1) the form of alienation of the character "I" in the novel "Mausim al-Hijrah ila as-Syamal", namely despair/feeling hopeless and wanting to die; and (2) the form of alienation of the character "Mustafa Said" in the novel "Mausim al-Hijrah ila as-Syamal", namely that he rarely socializes and has a private/secret space. Humans who experience alienation have various causes and symptoms, depending on the person's personality and living conditions. Then, the causes and symptoms experienced by humans produce various forms of alienation.